The discourse of “failed” women: a critical reflection toward standards of happiness in Indonesian society - Karolus, Meike Lusye; Betyarini, Angela Frenzia (The Indonesian Journal of Communication Studies, 2022)
The dominant standard of happiness in Indonesia is still rarely discussed as a crucial issue that oppresses, exploits, and excludes women. In that case, ideal happiness places a burden on women to play and fulfill their role in society. Instead of being critical, most women preserve the image of ideal women which is driven by the intersection of patriarchy, colonialism, feudalism, capitalism, and binary thought. The intersection of oppressive ideologies creates psychological and emotional torture for other women who are considered different or do not fit in with the standards (failed). The restrictions on space and social pressure are increasingly burdening women, creating emotional tension that produces specific lingering feelings (affects). This study discusses the contribution of queer-feminist knowledge in forming women’s knowledge to understand and accept their subtle experiences as those who are considered to be failures and how they create strategies to deal with society's standards of happiness. This research was conducted by combining textual analysis (Instagram’s posts) and empirical research (in-depth interview and testimonials) of urban women who live in Yogyakarta, Bali, Seoul, and Singapore. By using the affect theory approach and queer-feminist thinking, this research aims to distribute queer-feminist knowledge in intervening concepts and standards of happiness in Indonesian society that marginalize and perpetuate oppression toward women.